Integrating deep learning and digital literacy into reading instruction to achieve SDG 4: A study in a high school EFL education context in Central Java - Setyoningsih, Setyoningsih; Susanto, Dias Andris; Aldizeeri , Maram Miftah; Adeoye, Moses Adeleke (JOALL (Journal of Applied Linguistics and Literature), 2025)
This study investigates integrating deep learning approaches and digital literacy into reading instruction to support the achievement of Sustainable Development Goal 4 (Quality Education) among high school EFL students in Central Java, Indonesia. The study objectives were to evaluate the efficacy of deep learning-based reading strategies in improving students' comprehension, assess their digital literacy levels, and evaluate teachers' perceptions of integrating deep learning and digital literacy in EFL reading classrooms. One hundred seventy-eight tenth-grade students from three public high schools in Central Java participated in this study, which employed a mixed-methods sequential explanatory design.  A digital literacy questionnaire and reading comprehension pre- and post-tests were used to gather quantitative data.  Semi-structured interviews, teacher focus groups, and classroom observations were used to gather qualitative data.  After using immersive learning methodologies backed by digital media resources, pupils' reading comprehension scores significantly improved, according to quantitative studies. There was also a high correlation between students' reading competence and their digital literacy levels. The qualitative data showed greater student participation and high comprehension of the text as observed by teachers accompanied by enhanced engagement, critical thinking, and autonomy of students in reading activities. These results substantiate the integration of deep learning and digital literacy into reading lessons. It raises both cognitive and affective dimensions in EFL contexts. The significant study about pedagogical innovation emphasizes the SDGs, teacher training, and curriculum support that sustain tech-enhanced learning environments in Indonesian secondary schools.